2008
DOI: 10.1063/1.2952502
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of fast responding pressure sensitive microspheres

Abstract: The response times of pressure sensitive paint (PSP) and pressure sensitive microspheres to passing shockwaves were measured to investigate their ability to accurately determine pressure changes in unsteady flows. The PSPs tested used platinum tetra(pentafluorophenyl)porphine (PtTFPP), platinum octaethylporphine (PtOEP), and a novel set of osmium-based organometallic complexes as pressure sensitive luminophors incorporated into polymer matrices of dimethylsiloxane bisphenol A-polycarbonate block copolymer or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The optical microscopy images of the PS beads were taken using a confocal laser scanning microscope (Carl Zeiss, Thornwood, NY). The pressure and temperature responsiveness of the PS beads were measured using a dynamic flow system (the PMT survey apparatus) described in a prior publication . A mercury short arc lamp equipped with a band pass filter centered at 365 nm was used to excite the luminophors in these beads.…”
Section: Methodsmentioning
confidence: 99%
“…The optical microscopy images of the PS beads were taken using a confocal laser scanning microscope (Carl Zeiss, Thornwood, NY). The pressure and temperature responsiveness of the PS beads were measured using a dynamic flow system (the PMT survey apparatus) described in a prior publication . A mercury short arc lamp equipped with a band pass filter centered at 365 nm was used to excite the luminophors in these beads.…”
Section: Methodsmentioning
confidence: 99%
“…For reference, the response times of polystyrene microbeads (following previous procedures 25 are also included, which show that they are the largest response times, which is consistent with previous results. 1 The polystyrene and silica microbead response time comparison is also shown in Figure 4.…”
Section: B Response Time Resultsmentioning
confidence: 99%
“…[19][20][21] Hence, to develop a fast responding microbead, a compromise would have to be made between the thickness of the layer and the oxygen diffusion coefficient. Kimura et al 1 reported that the response times for 2 μm diameter polystyrene microbeads are estimated to range from 9.8 ms to 27.6 ms, which would be too slow for desired applications, such as measuring pressure changes in turbulent flows. This lead to initial research involving the synthesis of a new type of microbead using a highly porous silicon dioxide structure containing novel pressure-sensitive osmium complexes, with a much faster response time (Kimura et al 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Images of these pressure sensitive beads with a narrow particle size distribution can be seen in figure 15. The response time of conventional PSP film, the beads, and hollow porous silica micro spheres was also evaluated [119], and it was found that the response time of the silica spheres was two orders of magnitude shorter than that of the polystyrene beads, because no binder material was included in the hollow porous particles. Kim et al [114] fabricated oxygen sensitive particles with a diameter ranging from 2.2 to 3.9 µm using a dispersion polymerization method by synthesizing PtOEP with polystyrene.…”
Section: Dopant Dyes For Other Application (Partial Pressure Of Oxygen)mentioning
confidence: 99%